Hubungan Antara Tingkat Harga Diri Mahasiswa dengan Keikutsertaan Organisasi Kampus - Laili Sukmawati; Wigyo Susanto; Dwi Heppy Rochmawati (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Every campus must have an organization within it. Many students join organizations on campus and have no relationship with their self-esteem. Every campus surely has organizations within it. The research results show a relationship between self-esteem levels and campus organization participation among students of the Faculty of Economics at Universitas Islam Sultan Agung Semarang, with a p-value of 0.000 and a moderate correlation indicated by an r-value of 0.450. The research results indicate a relationship between self-esteem levels and campus organization participation among students of the Faculty of Economics at Universitas Islam Sultan Agung Semarang, with a p-value of 0.000 and a moderate correlation shown by an r-value of 0.450.